1984
DOI: 10.1073/pnas.81.13.3929
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymic ADP-ribosylation of specific mitochondrial polypeptides.

Abstract: The apparent NAD:protein ADP-ribosyl transferase activity of mitochondria and submitochondrial particles from beef heart and rat liver is simulated by a reaction sequence that consists of an enzymic hydrolysis of NAD to ADP-ribose (ADP-Rib) by NAD glycohydrolase(s) and a nonenzymic ADP-ribosylation of acceptor proteins by the free ADP-Rib formed. The nonenzymic ADP-ribosylation of mitochondrial proteins showed two pH optima and exhibited the same remarkable selectivity as the reaction with NAD. The predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
4

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 30 publications
6
58
4
Order By: Relevance
“…Non-enzymic mono-(ADP-ribosyl)ation has been reported by Hilz et al (1984) turnover of poly(ADP-ribose) (reaction q, Fig. 2a).…”
Section: Introductionmentioning
confidence: 85%
“…Non-enzymic mono-(ADP-ribosyl)ation has been reported by Hilz et al (1984) turnover of poly(ADP-ribose) (reaction q, Fig. 2a).…”
Section: Introductionmentioning
confidence: 85%
“…and 2, respectively) and in lanes 7 and 8 (as in lanes 3 and 4, respectively). It has been reported that ADP-ribosylation can occur in mitochondria by non-enzymatic transfer of ADP-ribose to protein acceptors [8]. When mitochondria were incubated with [32P]ADPribose in the presence of cyanide, there was no cyanide stimulation of ADP-ribosylation (not shown).…”
Section: Resultsmentioning
confidence: 94%
“…In an attempt to elucidate the controversy concerning ADP-ribosylation in mitochondria [7,8] data are presented here demonstrating that cyanide stimulates ADP-ribosylation in mitochondria or mitoplasts (inner mitochondrial membrane preparation stripped of outer membrane). Cyanide is a potent irreversible inhibitor of cytochrome c oxidase, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phenylmethylsulfonyl fluoride: SDS, sodium dodecyl sulfate. tion of acceptor proteins in the inner mitochondrial membrane in a nonenzymatic reaction [7]. Specific ADP-ribosylation of an ADPR acceptor protein may then trigger the release of Ca 2+ from mitochondria through regulation of a Ca 2* channel.…”
Section: Introductionmentioning
confidence: 99%